Pengaruh Kualitas Layanan terhadap Loyalitas Pelanggan Bamboo Coffee dan Resto di Lhokseumawe - Amanda Rizkillah; Suryani Suryani; Rahmawati Rahmawati (MBIA, 2020)
Bamboo Coffee and Resto become a restaurant that is great demand because it serves a variety of menu choices that continue to improve the quality of service to stay afloat and compete. This study discusses analyzing how to affect service quality on customer loyalty in Bamboo Coffee and Resto in Lhokseumawe. The sampling technique used was accidental sampling with a total sample of 94 consumers and multiple regression analysis as a data analysis technique. SERVQUAL Theory is a theory used to measure the quality of services, namely the dimensions of reliability (X1), responsiveness (X2), guarantee (X3), empathy (X4) and tangible (X5). The results of this study indicate the facts both simultaneously and simultaneously, this dimension has a very significant influence on customer loyalty.